A Cost Effectiveness Analysis Of Single Use And Reuse Dialyser Utilization In Hemodialysis Services For Kidney Failure Patients At Hospital X Stabat - Maas Lubis; Ermi Girsang; Sri Lestari Ramadhani Nasution (UNIVERSITAS PAKUAN, 2024)
The prevalence of Chronic Kidney Disease sufferers globally, including Indonesia, has increased every year. According to the 2018 Basic Health Research data, the prevalence of Chronic Kidney Disease in Indonesia is 0.38% of the population of Indonesia or around 713,783 people. The Indonesian Nephrology Association said that the use of reuse dialyzers is permitted with a maximum limit of 7 times of use, Indonesian 2 Renal Registry data shows that reuse dialyzers are mostly used with a frequency of 1-5 times. Manual cleaning of single-use and reuse dialyzers can have an impact on several aspects, including: dialysis adequacy and risk of infection. Putri Bidadari Hospital, Stabat has a problem with changing the reuse dialyzer to single use because if you use reuse, the used equipment is washed again. So by switching to single use, it is hoped that the output of hemodialysis will be better. However, by switching to single use, there is a possibility of additional/reduced costs per patient for each hemodialysis. This study aims to analyze the Cost Effectiveness of Using Single Use and Reuse Dialyzers for Hemodialysis Services for Kidney Failure Patients at Putri Bidadari General Hospital, a cross-sectional quantitative research design with a prospective and retrospective approach, involving 160 patients in 2023. Data were analyzed using Cost Effectiveness Analysis (CEA). The results of the analysis show that the cost efficiency of the Reuse dialyzer is proven to be lower than the Single Use dialyzer. While in producing changes in the outcome of creatinine, urea, and hemoglobin, the single use dialyzer is more effective than the reuse dialyzer. Hospitals also need to conduct an evaluation of the environmental impact of using both types of dialyzers, including medical waste and energy consumption.